2023
DOI: 10.5070/g60111266
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic and semantic interference in sentence comprehension: Support from English and German eye-tracking data

Abstract: A long-standing debate in the sentence processing literature concerns the time course of syntactic and semantic information processing in online sentence comprehension. The default assumption in cue-based models of parsing is that syntactic and semantic retrieval cues simultaneously guide dependency resolution. When retrieval cues match multiple items in memory, this leads to similarity-based interference. Both semantic and syntactic interference have been shown to occur in English. However, the relative timin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 113 publications
0
13
4
Order By: Relevance
“…The reading times of the immediately following spill-over region and of the pre-critical region were also of interest. Previous work using the present design (Mertzen et al, 2023;Van Dyke, 2007) has consistently found effects in the pre-critical region (we return to this point in the discussion sections). A further issue with German embedded clauses (also see Mertzen et al, 2023) was that, without an appropriate intervening phrase, the clause embedding would lead to two verbs appearing one after another (erzählt hatte, trank, literally 'told, drank').…”
Section: Methodsmentioning
confidence: 63%
See 4 more Smart Citations
“…The reading times of the immediately following spill-over region and of the pre-critical region were also of interest. Previous work using the present design (Mertzen et al, 2023;Van Dyke, 2007) has consistently found effects in the pre-critical region (we return to this point in the discussion sections). A further issue with German embedded clauses (also see Mertzen et al, 2023) was that, without an appropriate intervening phrase, the clause embedding would lead to two verbs appearing one after another (erzählt hatte, trank, literally 'told, drank').…”
Section: Methodsmentioning
confidence: 63%
“…The studies had 120 items with four conditions in a Latin square design shown in (2). The items were constructed following Van Dyke's (2007) items and partially re-used Mertzen et al's (2023) The comprehension of the sentences in (2) requires a memory retrieval operation at the verb trank ('drank') to retrieve its non-adjacent subject Witwer ('widower'). During this retrieval, the distractor Einbrecher ('burglar') / Verlust ('loss') might cause interference and impede comprehension.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations